Archives of Bessarabia (Confluenţe Bibliologice, 2022)
Briefly, information is presented that refers to the magazine Arhivele Bessarabiei, a prestigious publication with a high scientific standing that constitutes an inexhaustible source of new information for historians, geographers, theologians, ethnologists, sociologists, bibliologists. This magazine, along with other periodicals that circulated in interwar Bessarabia, contributed to the development of science, strengthening the moral and spiritual values of the native population.
Keywords: Archives of Bessarabia Magazine